2021
DOI: 10.3389/fmed.2021.699243
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Early Warning Model for Predicting the Death Risk of Coronavirus Disease 2019 Based on Data Immediately Available on Admission

Abstract: Introduction: COVID-19 has overloaded worldwide medical facilities, leaving some potentially high-risk patients trapped in outpatient clinics without sufficient treatment. However, there is still a lack of a simple and effective tool to identify these patients early.Methods: A retrospective cohort study was conducted to develop an early warning model for predicting the death risk of COVID-19. Seventy-five percent of the cases were used to construct the prediction model, and the remaining 25% were used to verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Fifty-five studies aimed to exclusively predict in-hospital mortality [ 2 , 11 , 14 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 29 , 30 , 31 , 32 , 34 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 50 , 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 79 ], while thirteen reported on combined outcome...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-five studies aimed to exclusively predict in-hospital mortality [ 2 , 11 , 14 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 29 , 30 , 31 , 32 , 34 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 50 , 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 79 ], while thirteen reported on combined outcome...…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four nomograms were derived and validated (in different patients from the same institution) in the same study; random training test splits [ 14 , 17 , 18 , 19 , 23 , 24 , 30 , 32 , 33 , 41 , 45 , 50 , 51 , 55 , 59 , 60 , 61 , 62 , 63 , 65 , 66 , 67 , 71 , 75 , 76 , 77 ] and temporal splits [ 15 , 43 , 44 , 46 , 53 , 70 ] were performed in fourteen and five studies, respectively. One study performed validation by leave-one-hospital-out cross validation [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four variables were used to construct the prognosis prediction model for these patients, and we discovered that it had a high predictive value, the AUC was higher than 0.9, and high sensitivity and specificity. Numerous studies had shown that age was an independent risk factor for a poor outcome with COVID-19 (14)(15)(16)(17). The following are possible explanations: chronic illnesses such as hypertension, diabetes, and coronary heart disease become increasingly prevalent as people become older (18); the elderly's baseline level of proinflammatory cytokines in tissues and circulation increases with age, and the body's immune response to pathogenic threats or tissue damage is also delayed (19); the angiotensin-converting enzyme 2 (ACE-2) receptor is required for the COVID-19 virus to enter cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…In the early phase of the COVID-19 pandemic, meta-analysis studies documented that dyspnea, anorexia, dizziness, and fatigue were significantly associated with the critical outcome [ 3 ]. Likewise, oxyhemoglobin saturation by pulse oximetry (SpO 2 ), body temperature, and mean arterial pressure on admission can also predict COVID-19 patients with a high probability of mortality [ 4 ]. The COVID-19 timeline was described as the median duration from illness onset to dyspnea of 8.0 days (interquartile range, 5.0–13), whereas from onset of symptoms to first hospital admission was 7.0 days (4.0–8.0) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%